PENAMPILAN PERTUMBUHAN AYAM BANGKOK STARTER YANG DIBERI PAKAN DENGAN LEVEL PROTEIN BERBEDA - Mokodongan, Aditya R.; Nangoy, F.; Leke, Jein Rinny; Poli, Zulkifli (ZOOTEC, 2017)
THE GROWTH OF PERFORMANCE â€œBANGKOKâ€ CHICKEN AT THE STARTER PHASE GIVEN FEED IN LEVELS OF DIFFERENCE PROTEIN. This study was conducted to evaluate the levels of protein in ration affecting consumption, average daily gain, feed conversion and mortality of â€œBangkokâ€ chicken at the starter phase. Birds used in this study were 36 chicken at the age of 2 weeks old. Treatments in this study were rations with protein levels of 18 percents (Ration A), 20 percents (Ration B), and 22 percents (Ration C).Variables observed were feed consumption (g/h/d), Average daily gain (g/h/d), feed conversion and mortality (percents). Method of completely randomized design were applied in this study using 3 treatments with 6 replications at each treatment. Each treatment and replication was filled 2 chicken of â€œBangkokâ€ strain. Results of this study showed that protein levels of 18 to 22 percents in the diets did not affect feed consumption, average daily gain, feed conversion and mortality. Therefore, it can be concluded that the protein levels of 18 to 22 percents in the diets had the same responses in growing performance of â€œBangkokâ€ strain at starter phase.Kata Kunci:â€œBangkokâ€ strain chicken, growing performance, protein levels.